Prevalence of urinary incontinence and its associated predictor and Self-care behavior among the elderly females in Chaiyaphum Province, Thailand: Cross-sectional study - Patchareepon Chompoowisate; Sumattana Glangkarn; Chaloemporn Namyota (Journal of Education and Health Promotion, 2024)
BACKGROUND: Urinary incontinence (UI) has been overlooked by elderly females because it is considered an embarrassment and physical dysfunction that occurs naturally in older women. However, UI is problematic if symptoms are ignored, and the condition becomes chronic. MATERIALS AND METHODS: This cross-sectional descriptive research was conducted in a community context using semi-structured interviews as data collection methods. The interviews involved 1475 elderly females who live in Muang district, Chaiyaphum province and were analyzed by Chi-square, Pearson Product Moment Correlation Coefficient, Stepwise multiple regression, Bivariate and Multivariate at 0.05 statistical significance. RESULTS: The study found a 30.37% prevalence of UI. Nine factors are related to the cause: Pelvic muscle exercise, water intake, caffeine and alcohol intake, diabetes, environmental obstacles, activities, constipation, urination frequency, and exercise. Elderly females who had their highest education at primary school to high school also had the possibility to experience 64% and a diploma had the possibility to experience 68% less UI than illiterate ones. The elderly females who had more than 23 kilograms per square meter (kg/m2) for body mass index (BMI) tend to have 2.64 times more than those who had 18.5–22.9 kg/m2 at 0.05 statistical significance. UI self-care behavior on overall prediction was moderate, whereas behavioral change and self-care performance were high. CONCLUSION: Nine factors are related to this cause. The possibility is also related to educational level and BMI. The overall UI self-care behavior showed a moderate level of prediction, but a high level of behavioral change and self-care performance.